Community Volunteers’ Care for Older Adults (Lansia) in Indonesia: The Symbolic Efficacy of Community Health Meetings (Posyandu) - Porath, Nathan; Schröder-Butterfill, Elisabeth; Insriani, Hezti; Larastiti, Ciptaningrat (Humaniora, 2024)
Community healthcare in Indonesia relies on volunteers who engage their clients outside fixed health facilities with limited resources and formal training. These volunteers are called cadres who learn their tasks to improve community wellbeing through ongoing engagement and without prior formal skills. They are drawn from the community to serve the community. This paper is based on field research carried out with cadres through interviews and visits to integrated health meetings (posyandu lansia) held by primary healthcare centres for older adults in villages in Jakarta and Yogyakarta. The paper first discusses the recruitment requirements and incentives for being a healthcare volunteer. It suggests that both recruitment and incentives are rooted in community values of helping and doing good for the community. Volunteer cadres must have a direct normative and semiotic connection with clients, as they must be members of the community who speak the same language and understand local norms. In line with this community-centred approach, the paper then focuses on the health efficacy of posyandu by viewing them as a recurring, structured symbolic event held in the village. The argument is made that a more qualitative approach should be taken to understanding the efficacy of these meetings, drawing on research methods from the anthropology of ritual (symbolic and therapeutic) healing.